XII International Conference on Mathematics, Science and Technology Education: conference report - Arnold Kiv; Serhiy Semerikov; Vladimir Soloviev (Academy of Cognitive and Natural Sciences, 2021)
This article represents the proceedings of the XII International Conference on Mathematics, Science and Technology Education (ICon-MaSTEd 2020) held at the Kryvyi Rih State Pedagogical University, Ukraine, 15-17 October 2020. Background information and the organizational structure of the meeting, a summary of the papers, and acknowledgements of the contributions of the many people who made the conference a success are presented.